Into the heartlands : a Black Panther graphic novel - Brown, Roseanne A. (Graphix, an imprint of Scholastic, 2022)
"Twelve-year-old Shuri is a lot of things. Scientist. Princess. All around cooler person than her pain-in-the-butt big brother, T'Challa. Shuri knows she could do so much more to help Wakanda, but everyone is obsessed with the prince because he's the next Black Panther. That is, until Soul Washing Day, one of the most important rituals of Wakandan society. When an argument between T'Challa and Shuri leads to one of Shuri's inventions accidentally destroying the sacred ceremony site, chaos reigns instead of prosperity. Suddenly the people of Wakanda, including her mother the queen, are becoming sick! Could this be a curse from the ancestors? Desperate to save her mother, Shuri dives into research and finds an answer hidden deep in an ancient children's myth. It may be nothing more than a fantasy, but with the sickness spreading each day, the young princess must trust her instincts and travel deep into the mysterious Heartlands to save her family and her kingdom."--Back cover.